Peningkatan Kemampuan Siswa Kelas 4 di SDN Betoyoguci Kecamatan Manyar Kabupaten Gresik Dalam Membaca Peta Lingkungan Pada pelajaran Ilmu Pengetahuan Sosial Melalui Metode Inquiry - Mawardah, Sakinah; Adi, Titok Waskito (JURNAL WAHANA PENDIDIKAN DASAR, 2016)
The problem faced by the student of grade 4 semester 1 SD Negeri Betoyoguci Manyar District of Gresik is the low mastery os social science on basic competence reading maps local neighborhood (district/city, province) using a simple scale. Based on the problems, the reaserch questions that can be revealed is: how to increase learning achievement of social science on basic  competence reading maps local neighborhood (district/city, province) using a simple scale through methods of inquiry in class 4 semester 1 SD Negeri Betoyoguci Subdistrict Manyar Gresik. This research was done in class 4 semster 1 SD Negeri Betoyoguci District of Manyar, the number of students in grade 4 were 28 people, the condition of specificity allow the student ability level and absorption of this students vary greatly. Researchers are fourth grade teacher at SDN Betoyoguci Manyar District of Gresik. In accordance with the formulation of the problems and the purpose of research it can generally be conclude that result for students in elementary school Betoyoguci Manyar District of Gresik, can improve through learning by using methods inquiry.